3D visualization of subsurface objects from La brea tar pits, Los Angeles, CA. (March 2021) - Hill, Kristiane M.; Swift, Jennifer N.; Howard, Carrie; Farrell, Aisling B.; Lindsey, Emily L.
Abstract: Accurate determination of geographic location and three-dimensional orientation of objects recovered from the subsurface has numerous applications in the environmental, engineering and historical sciences, to name but a few major areas of research. Studies relying on accurate representations of natural and man-made objects in-situ prior to removal from soil, rock, and other substrates exist in a variety of disciplines. A case study exploring geolocation and visualization of vertebrate fossils using three-dimensional geospatial technologies provides an example method of establishing accurate geolocation and visual depiction of objects found underground. Interpretation of archaeological and paleontological finds is enhanced through knowledge of precise relative position of objects. The 3D objects were constructed through a 3D scanning process and a procedure for digitally reconstructing the real-world placement of the objects in the subsurface was developed. The problems and solutions described in this study can be adapted for use in a variety of scientific fields.